2009
DOI: 10.1002/etc.88
|View full text |Cite
|
Sign up to set email alerts
|

Effects of egg order on organic and inorganic element concentrations and egg characteristics in tree swallows, Tachycineta bicolor

Abstract: The laying order of tree swallow eggs was identified from the Housatonic River, Berkshire County, Massachusetts, USA, and eggs were chemically analyzed individually to document possible effects of laying order on organic contaminant and inorganic element concentrations. Effects of laying order on other parameters such as egg weight, size, and lipid and moisture content also were assessed. Some effects of egg order on total polychlorinated biphenyls (PCBs) were detected, but the effect was not uniform across in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…The relationships of contaminant exposure level and clutch mass with the reduction in maternal burden over the laying period could also have consequences on laying order effects, if the decreasing burden results in declining egg concentrations. Reviews of studies on laying order effects on egg contaminant concentrations have found that there is no consistent pattern for egg contaminants over the laying sequence, and the majority of studies show no significant laying order effects [7,39]. This is not surprising, as individual variation in maternal contaminant burden and reproductive investment could result in variation in laying order effects among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships of contaminant exposure level and clutch mass with the reduction in maternal burden over the laying period could also have consequences on laying order effects, if the decreasing burden results in declining egg concentrations. Reviews of studies on laying order effects on egg contaminant concentrations have found that there is no consistent pattern for egg contaminants over the laying sequence, and the majority of studies show no significant laying order effects [7,39]. This is not surprising, as individual variation in maternal contaminant burden and reproductive investment could result in variation in laying order effects among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Eggs were collected shortly after the clutch was completed during the last week in May and the first week in June, the contents placed in chemically-clean jars, and frozen at -20°C until chemically analyzed. The specific eggs collected were taken haphazardly from the completed clutch; there is no evidence that laying order or stage of incubation affects total PCB concentrations in a predictable manner (Custer et al 1997(Custer et al , 2010b. In 1990s, eggs, 'pippers' consisting of pipping eggs or just-hatched nestlings within a day of hatching, and 12-day-old nestlings (±1 day of age) were collected, whereas in 2010s, eggs and 12-day-old nestlings were collected.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of the present study was to determine whether PCB 77 increased mortality in tree swallows eggs and to assess other impacts of this congener, particularly heart defects in the developing embryo. The Upper Hudson River was considered contaminated based on previous studies and measurements of PCBs in eggs collected from nests in that region [29][30][31]. Embryos in these eggs were considered environmentally exposed and were not dosed with PCB 77 treatments.…”
Section: Introductionmentioning
confidence: 99%